Blurring the line between addenda and heteroatoms in a giant polyoxotungstotellurite. Issue 72 (21st August 2019) - Liu, Jin-Xiu; Izarova, Natalya V.; Kögerler, Paul
Abstract : An unusually high tellurium content in [H4 TeIV48WVI78O372 ] 80− leads to Te centers assuming both the traditional heteroatom as well as the addenda functionalities. Abstract : The 3.5 nm-sized polyanion [H4 TeIV48WVI78O372 ] 80−, exhibiting an exceptionally high Te : W ratio, expands the structural role of Te IV ions from classical heterogroups within polyoxotungstate subunits to addenda ions. Investigations on the self-assembly conditions, proceeding in a simple one-pot reaction, point to the pH as one critical factor for circumventing this limitation.